‘What’s the word? That’s the word!’: linguistic features of Filipino queer language - Mark Bedoya Ulla; Jonathan Marcos Macaraeg; Renz E. Ferrera (Cogent Arts & Humanities)
Understanding queer language, which includes knowing its meaning and its applications, is essential not only for understanding sexuality and fostering language inclusivity but also for acknowledging the multifaceted uses of language across all societal groups. This study explored the semantic nuances and underlying patterns of Filipino queer language using Word Sense Disambiguation (WSD). Using content analysis on the data from publicly available posts and comments on Facebook and Twitter, the findings uncovered distinct characteristics of Filipino queer language, encompassing affixation, appropriation, clipping, association, mutation, neologism, recontextualization, and stylized reversal with affixation. The findings underscore the vibrancy and adaptability of Filipino queer language, reflecting the LGBTQIA + community’s ability to use language as a tool for self-expression and cultural relevance. Additionally, the findings highlight the significance of understanding queer language not only as an identity expression for LGBTQIA + individuals but also as a means to promote linguistic inclusivity for all groups in society. We discuss the implications, and we offer recommendations.